Pengaruh Motivasi, Work Overload, dan Work Life Balance terhadap Kinerja Karyawan Produksi PT Praoe Lajar - Anisa Azhari; Nurul Dwi A; Fariska Anggun S; Viola Cindy M (JURNAL RISET MANAJEMEN (JURMA), 2025)
The purpose of this research is to determine the influence of motivation, work overload, and work-life balance on the performance of production employees at PT Praoe Lajar. The background of this research arose due to the decline in the company’s production targets that occurred in the last six months. The technique applied in this research is quantitative, through the use of several data analysis composed of classical assumption testing, validity testing, reliability testing, then multiple linear analysis, then the coefficient of determination and t-test. The sample used consisted of 55 respondents who were employees of cigarette production 10 at PT Praoe Lajar Semarang. Primary data was obtained through the distribution of questionnaires, while through the use of SPSS Version 26 in conducting data analysis. Through the research that has been produced, it is stated that work motivation, work overload, and work-life balance have a positive and significant influence on employee performance aspects. This indicates that if motivation and work-life balance are increased, and the workload of employees can be managed well, then employee performance will be better.